Mapping Miskitu subsistence land use change in Concejo Territorial Katainasta, Honduras - Tappan, Taylor A.; Herlihy, Peter H. (Revista Geográfica de América Central., 2018)
Understanding the large-scale spatial patterns of natural resource use in indigenous homelands is critical for guaranteeing indigenous peoples’ ancestral land rights, designing effective conservation policies, and promoting good governance in Central America. However, few studies have mapped the diachronic distribution of indigenous communities’ resource use in these areas. Here we present a case study describing the spatial functionality of the Concejo Territorial Katainasta (CTK)–the first indigenous territorial jurisdiction in Honduras to receive an intercommunity land title. Two participatory research mapping (PRM) studies–the first in 1992 and the second in 2014-15–mapped the spatial patterns of Miskitu subsistence activities in CTK. The results were subsequently converted into a geographic information system (GIS) that allowed for spatial and temporal comparisons of Miskitu subsistence livelihoods in CTK before and after the titling process. Here we focus on the spatial parameters of three Miskitu subsistence livelihoods: agriculture, hunting and fishing. Analysis of results suggests that 1) the 2014-15 subsistence use areas for Miskitu communities in CTK have not diverged dramatically from those of the 1992 study, and 2) the new legal boundaries of CTK adequately encompass the subsistence use areas of its constituent communities and recognize the historical overlaps in Miskitu resource use and tenure patterns.